MOBILE VIEWER SYSTEM DESIGN FOR EXTENDING MEDICAL DIAGNOSTIC IMAGING NETWORKS - Azizul Azizan; Azi Azwady Jamaludin; Hafiza Abas; Salwani Mohd Daud; Yusnaidi Md Yusuf; Hadhrami Ab. Ghani (PERINTIS eJournal, 2021)
Medical diagnostic imaging or commonly known as DICOM has been developed to meet the needs of manufacturers and users of medical imaging equipment for data interconnection between devices and modality (i.e. medical imaging) on standard networks. The medical data and image that is captured as DICOM data attributes, can be transmitted and processed between various DICOM devices and software, hence limiting the access of DICOM data to non-standardized DICOM systems. Herein, an internet based Picture Archiving and Communication System (PACS) server with web viewer with the capability to extend the DICOM network through network gateway is demonstrated. It enables the web viewer to display the DICOM image using plugin, directly from DICOM archives. Further functionality of the server has enabled the implementation of relational database plugin and the stored source can be shared by using normal mobile application. This paper discusses the system design of stand-alone mobile viewer for DICOM, based on web service with relational database and an internet based PACS server based on client server architecture. The outcome of the study enables displays of medical images within a non-DICOM networks via mobile web-based application.